Improvement of Daptomycin Production in Streptomyces roseosporus through the Acquisition of Pleuromutilin Resistance. (10th September 2013) - Li, Linli; Ma, Tingmei; Liu, Qing; Huang, Yuqi; Hu, Changhua; Liao, Guojian
Abstract : Daptomycin, a cyclic lipopeptide antibiotic produced by Streptomyces roseosporus, displays potent activity against a variety of gram-positive pathogens. There is a demand for generating high-producing strains for industrial production of this valuable antibiotic. Ribosome engineering is a powerful strategy to enhance the yield of secondary metabolites. In this study, the effect of a diterpenoid antibiotic pleuromutilin resistance mutation on daptomycin production was assessed. Spontaneous pleuromutilin-resistant derivatives of S. roseosporus were isolated. Sequencing of rplC locus (encoding the ribosomal protein L3) showed a point mutation at nt 455, resulting in the substitution of glycine with valine. G152V mutants showed increased production of daptomycin by approximately 30% in comparison with the wild-type strain. Its effect on daptomycin production was due to enhanced gene transcription of the daptomycin biosynthetic genes. In conclusion, pleuromutilin could be used as a novel ribosome engineering agent to improve the production of desired secondary metabolites.